Non-deletional alpha thalassaemia: a review of emerging therapy - Khairil Wahidin, Nurfhaezah; Lai, Mei I. (Universiti Putra Malaysia, 2021)
More than seventy non-deletional α-thalassaemia mutations have been reported and they usually exhibit more severe clinical presentations compared to their deletional counterparts. Conventional treatment aims to manage the symptoms of the disease through red blood cell transfusion, but this has its own set of complications. For the time being, the only cure for thalassaemia is bone marrow transplantation, hence, it is a priority to explore other potential treatment methods. Novel gene editing methods could potentially be a long-term treatment option for this single gene disorder. This manuscript provides an overview of recent breakthroughs in non-deletional α-thalassaemia treatment, including intrauterine transfusion, cord blood transplantation, gene therapy, and several genome modification techniques, to contribute to the overall knowledge in not only ameliorating the condition of α-thalassaemia, but also to find a cure.